The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.10186
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Large Granular Lymphocytic Leukemia as a Cause for Severe Neutropenia

Abstract: Large granular lymphocytic (LGL) leukemia is a rare, indolent disease that can cause destruction of neutrophils. We discuss the case of a previously healthy 63-year-old male who presented with severe, recurrent febrile neutropenia, in whom three bone marrow biopsies over 13 months failed to produce a diagnosis. He presented to our facility with persistent fevers and an absolute neutrophil count of 20 cells/mm 3 (reference range 1,700-7,000 cells/mm 3). A fourth bone marrow biopsy did not show clonal proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…It should be noted that in medical literature some case reports of patients with neutropenia and recurrent infections ultimately diagnosed with T-LGL leukemia can be found [9,10]. In contrast with the patient in our case, those patients had a larger number of infections and were younger.…”
Section: A Diagnosis Of T-contrasting
confidence: 67%
“…It should be noted that in medical literature some case reports of patients with neutropenia and recurrent infections ultimately diagnosed with T-LGL leukemia can be found [9,10]. In contrast with the patient in our case, those patients had a larger number of infections and were younger.…”
Section: A Diagnosis Of T-contrasting
confidence: 67%
“…From selected articles ( n = 20), data were collected into a standardized form including publication year, source, number of total patients and divided by sex, number of subjects with autoimmune disorders, hematological malignancies, or cancers, and Vβ usage by flow cytometry ( Table 2 ) [ 41 , 42 , 46 , 75 , 76 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. A total of 533 T-LGL leukemia patients were evaluable for Vβ usage analysis, and sex was available in 524 subjects: 308 of them were males (58.8%) and 216 females (41.2%) with a male:female ratio of 1.4, as already described in smaller cohorts [ 1 ].…”
Section: Literature Searchmentioning
confidence: 99%
“…Studies were included when: (1) the year of publication was between 2011 and 2021; (2) the studies were conducted on humans and reported clinical data and Vβ usage by flow cytometry; and (3) the studies were on T-LGL leukemia (Figure 2). From selected articles (n = 20), data were collected into a standardized form including publication year, source, number of total patients and divided by sex, number of subjects with autoimmune disorders, hematological malignancies, or cancers, and Vβ usage by flow cytometry (Table 2) [41,42,46,75,76,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. A total of 533 T-LGL leukemia patients were evaluable for Vβ usage analysis, and sex was available in 524 subjects: 308 of them were males (58.8%) and 216 females (41.2%) with a male:female ratio of 1.4, as already described in smaller cohorts [1].…”
Section: Literature Searchmentioning
confidence: 99%